2013
DOI: 10.3390/ijms140917536
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Blood Flow in Hepatocellular Carcinoma: Correlations of Computed Tomography Perfusion Imaging and Circulating Angiogenic Factors

Abstract: Hepatocellular carcinoma (HCC) is a highly vascular tumor through the process of angiogenesis. To evaluate more non-invasive techniques for assessment of blood flow (BF) in HCC, this study examined the relationships between BF of HCC measured by computer tomography (CT) perfusion imaging and four circulating angiogenic factors in HCC patients. Interleukin 6 (IL-6), interleukin 8 (IL-8), vascular endothelial growth factor (VEGF), and platelet derived growth factor (PDGF) in plasma were measured using Bio-Plex m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The prospect of predicting long-term outcomes following TACE based on pre-treatment radiologic features of the tumour is not a novel concept in HCC [ 13 ]. However this is the first study to comprehensively evaluate radiologic predictors relating to hypoxia and neo-angiogenesis on routine diagnostic CT scans without the need to extrapolate complex perfusion parameters [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prospect of predicting long-term outcomes following TACE based on pre-treatment radiologic features of the tumour is not a novel concept in HCC [ 13 ]. However this is the first study to comprehensively evaluate radiologic predictors relating to hypoxia and neo-angiogenesis on routine diagnostic CT scans without the need to extrapolate complex perfusion parameters [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Newly formed vasculature demonstrates increased permeability, tortuous course and wider luminal diameters compared to normal vessels, which can be easily detected on arterial CT sequences [ 14 ], often in form of aberrant AV shunting [ 18 ]. The emergence of ITN is an equally common finding in HCC and a surrogate marker of highly proliferating tumours that fail to maintain the required nutrient and oxygen supply [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and in vivo studies investigated the connection between PDGF and HCC (Table 1) [18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41]. In vitro studies showed a 7-fold increase in total PDGFR-alpha levels in HCC cells when compared to normal hepatocytes and a rise in chemosensitivity under normo- or hypoxic conditions when PDGF is repressed [18,19,20,21,22,24,25,26,28].…”
Section: The Specific Role Of Platelet-derived Growth Factormentioning
confidence: 99%
“…Chen et al evaluated blood flow in HCC using CT perfusion imaging 7 . Dynamic contrast-enhanced MRI 8 and diffusion MRI imaging 9 have also been used to evaluate blood flow in HCC.…”
Section: Introductionmentioning
confidence: 99%